Pembelajaran al-Qur’an Secara Digital: Pergeseran Sistem Isnad dan Peneguhan Otoritas Baru - Abdul Majit; Miski Miski (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
This research analyzes the phenomenon of changes in the isnad system in learning on the Qur’an on the Qara'a mobile application. This mobile application provides Al-Qur'an learning services that are supported by machine learning and artificial intelligence to correct the user's reciting of the Qur'an so that they have a "teacher" studying the Qur'an anywhere and anytime. The question then is, why has there been a change in the isnad system in transmitting scientific reciting of the Qur'an to the Qara'a mobile application, and what are the implications caused by this? In explaining the things that have been mentioned, this research uses a qualitative approach with a descriptive-critical analysis model; this method necessitates a pattern of depiction that does not merely present data objectively but also explains the implications of findings from related data. This research shows that changes in the isnad system in transmitting scientific reciting of the Qur'an are inevitably caused by mediamorphosis with the development of information and communication technology. In this context, this change occurs because of four main things, namely industry needs, demands for other technological needs, supporting legal actions and regulations, and societal pressure. The implications of this change occur in the process of mediamorphosis of the transmission media of reciting Al-Qur'an scholarship or even all of the transmission media of Islamic scholarship and the emergence of machine learning and artificial intelligence as new religious authorities.